Immune cells in thyroid adenoma and carcinoma: uncovering a hidden value of assessing tumor-host interplay and its potential application in thyroid cytopathology - Omelianenko, Iryna; Kobyliak, Nazarii; Falalyeyeva, Tetyana; Seleznov, Oleksii; Botsun, Pavlina; Ostapchenko, Lyudmila; Korotkyi, Oleksandr; Domylivska, Liudmyla; Tsyryuk, Olena; Mykhalchyshyn, Galyna; Shapochka, Tetiana; Sulaieva, Oksana (Frontiers in Molecular Biosciences, 2025)
IntroductionAlthough the role of tumor immune microenvironment (TIME) in thyroid cancer is well established, little data exists about the differences in immune cell presence in thyroid adenomas and carcinomas. We assume that immune cell density could be an additional diagnostic criterion for differentiating benign and malignant tumors in thyroid aspirates.AimThe current study compared the immune contexture of thyroid adenoma (TA) and thyroid carcinoma (TC) in histological and cytological specimens of III-V categories.Materials and methodsThis pilot study included 72 cases (36 of TA and 36 of TC) with verified histological diagnosis and pre-operative cytology corresponding to categories III, IV and V according to the Bethesda system for reporting thyroid cytology. The number of CD8+, CD68+ and CD163+ cells was assessed in histological samples of TA and TC with further comparison to cytological specimens. Besides, the expression of STAT6 and SMAD4 as potential regulators of TIME was evaluated in the study.ResultsTC demonstrated an immune-rich profile representing abundant tumor-associated CD8+ lymphocytes, CD68 and CD163+ macrophages. In contrast, TA represented mostly a low immune cell infiltration. The higher immunogenicity of TC was accompanied by the more profound expression of STAT6 and SMAD4 in tumor cells. The number of immune cells in cytological specimens correlated with CD8+ (r = 0.693; p < 0.001) and CD163+ cells (r = 0.559; p < 0.001) in histological samples, reflecting the differences in the tumor immune microenvironment between benign and malignant thyroid neoplasms.ConclusionTC demonstrated high immunogenicity compared to TA, which correlated to the number of immune cells in cytological specimens. The number of immune cells in thyroid cytology samples could be an additional criterion in cytological diagnostics for III-V Bethesda categories. Further investigations are needed to validate the findings of the study.